Molecular Docking of ftsZ Protein of Staphylococcus aureus to Indonesian Herbal Compound - Monica, Maria Diyan; Erlina, Linda; Fadilah, Fadilah; Paramita, Rafika Indah (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2024)
Microbial resistance to antibiotics is a growing global problem, and new antibacterial agents are needed to overcome this. One of the bacteria with a high level of resistance is Staphylococcus aureus. Herbal compounds are an alternative as a source of new antibacterial agents. Molecular docking can be used in screening herbal compounds that can become new antibacterial agents against Staphylococcus aureus. Virtual screening was conducted using Ligandscout, and molecular docking was conducted via Autodock. LigPlot was used to analyze the interaction between hit compounds to the protein target, and finally, the pharmacokinetic characteristics were assessed in SWISSADME and ADMETsar programs. From 1377 compounds in the Indonesian Herbal Database, 12 hit compounds have an affinity to the target protein ftsZ of Staphylococcus aureus. Further analysis of the interaction with target protein and pharmacokinetics properties considers Alpha Santalol a compound with good potential for further development as an antibacterial agent against Staphylococcus aureus. However, in vitro and in vivo study is needed to validate this result.